(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
A spectrophotometric method is developed for the determination of some drugs containing amino groups (sulfacetamide sodium, lidocaine and terbutaline sulfate) based on their reaction with p-chloranilic acid reagent in an organic medium forming colored charge transfer complexes. The complexes have maximum absorptions at 530 and 527 nm for sulfacetamide sodium and lidocaine respectively, but terbutaline sulfate gave two maximum absorptions at 529 and 319 nm. Beers law is obeyed over the concentration range of 10-60 µg.ml-1 for sulfacetamide sodium and lidocaine and 5-70 µg.ml-1 for terbutaline sulfate. The molar absorptivity values are 0.94—103, 0.913—103 L.mol-1.cm-1 for sulfacetamide sodium and lidocaine respectively while terbutaline sulfate gave 0.987—103 L.mol-1.cm-1 at 529 nm and 7.407—103 L.mol-1.cm-1 at 319 nm with accuracy range between 100.20% and 101.42% and RSD better than 3.15% for all drugs. The method is applied successfully for determination of these drugs in pharmaceutical formulations and compared favorably with British Pharmacopeia standard methods. F and t tests are less than the tabulated values at 95% confidence level.